COMMUNICATIVE STYLES IN CLASSROOM MATERIALS: A LINGUISTIC ANALYSIS OF ELEMENTARY EFL TEXTBOOK CONVERSATIONS - Jihananda Cahya Bagaskara; Ahdi Riyono; Rusiana (Indonesian EFL Journal, 2025)
This study investigates the language styles used in the dialogues of the “Look and Say” section in the "My Next Words Grade 5 Student’s Book for Elementary School.". the author conducted this study due to the rarely explored language styles in elementary school student books, particularly within the context of the Merdeka curriculum. Through this study, the author aimed to identify and describe the language styles and their functions in the dialogues of the specified textbook section. A qualitative methodology was employed, utilizing the language style theory of Joos and Holmes's theory on language functions. Data were collected through documentation analysis using content analysis. This study revealed that all 23 dialogues used a casual language style (100%). The functions identified were expressive (57%), referential (22%), directive (17%), and phatic (4%). In this study, the author concluded that the dialogues predominantly used a casual style, emphasizing emotional engagement and information delivery. It suggests incorporating more diverse language styles to enhance educational dialogues. Keywords: Language Style; Language Function; Student Book; Dialogue.